Towards ‘languages for all’ in England: the state of the debate - Hagger-Vaughan, Lesley (Taylor & Francis, 2016)
Whether the study of languages should be a core element of a balanced and broadly based curriculum for all pupils in England’s 11–16 state-funded secondary schools is also part of a wider debate concerning how to harness England’s rich linguistic and cultural diversity and improve the quality and range of language skills of the country. While learning a second language throughout compulsory schooling is increasingly the norm across the world, fewer than 50% of 14–16 year olds in state-funded schools in England gained a modern language qualiﬁcation (General Certiﬁcation of Secondary Education or GCSE) in 2015. From 2015, recent government education policy has required the majority of pupils commencing secondary school to study a language to GCSE level, suggesting that schools who do not comply will be unable to gain the top inspection grade. This paper reviews the state of the debate examining divergent and contradictory perspectives within education policy and in the literature. It concludes by setting out six conditions for achieving this policy goal for enabling secondary schools to successfully implement a coherent and relevant languages curriculum for all young people, such that they can develop the linguistic and intercultural competencies needed to contribute to and thrive in increasingly diverse local and global communities.